(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Immunoglobulin A nephropathy (IgA nephropathy) is one of the most common forms of chronic glomerulonephritis in children and adolescents. The disease is characterized by the deposition of IgA in the mesangial regions of the glomeruli, leading to the development of an inflammatory process and impaired renal function. Despite its prevalence, the pathogenesis of the disease remains incompletely understood, and its clinical course is highly variable — ranging from asymptomatic hematuria to rapidly progressive renal impairment. Therefore, early diagnosis and optimal therapy are crucial to prevent progression to chronic kidney failure.